Uncovering misperceptions of social inequalities: what matters most, objective class or subjective social status? - Melli, Giacomo; Azzollini, Leo (Frontiers in Sociology, 2025)
Perceptions of social inequality are shaped not only by individuals’ objective social class but also, and more powerfully, by their subjective social status. Drawing on data from the International Social Survey Programme (ISSP) covering 35 countries and 96 country-years between 1992 and 2019, this study disentangles the distinct and interactive effects of class and subjective status on how people perceive social inequality. While individuals in lower objective classes are somewhat more likely to perceive society as unequal, this effect diminishes once subjective social status is considered. Subjective status proves to be a significantly stronger predictor: individuals who perceive themselves on the lower rungs of society consistently perceive social structures as being highly unequal. When class and status align, their effects on perceived inequality reinforce each other; when they diverge, subjective status predominates. This highlights the significance of integrating subjective dimensions into the study of social stratification. These findings contribute to a growing literature emphasizing the sociopolitical relevance of subjective evaluations of social position, and show that considering class and status together provides a more comprehensive understanding of how inequality is perceived.